2016
DOI: 10.1111/acer.13099
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Acamprosate and Escitalopram on Ethanol Consumption in Mice

Abstract: Background Major depression is one of the most prevalent psychiatry comorbidities of alcohol use disorders (AUD). Since negative emotions can trigger craving and increase the risk of relapse, treatments that target both conditions simultaneously may augment treatment success. Previous studies showed a potential synergist effect of FDA approved medication for AUD acamprosate and the antidepressant escitalopram. In this study, we investigated the effects of combining acamprosate and escitalopram on ethanol consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…In a 2-bottle choice version of the 2 hr access DID test, male C57BL/6J mice showed no reductions in intake of 15% ethanol following repeated daily injections of 400 mg/kg acamprosate. Mice had previously been acclimated to the ethanol choice for 14 days, and lack of response was found regardless of whether or not the mice had been exposed to chronic unpredictable stress 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In a 2-bottle choice version of the 2 hr access DID test, male C57BL/6J mice showed no reductions in intake of 15% ethanol following repeated daily injections of 400 mg/kg acamprosate. Mice had previously been acclimated to the ethanol choice for 14 days, and lack of response was found regardless of whether or not the mice had been exposed to chronic unpredictable stress 32 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the model of sucrose consumption described in this study is different to the model of sucrose consumption commonly used for measuring depression-like behaviors. The later model generally involves administering lower concentrations of sucrose to mice for short periods (once weekly or for a few days at a time) (e.g., see Benturquia et al, 2007;Covington, Vialou, LaPlant, Ohnishi, & Nestler, 2011;Ho et al, 2016). However, the DID model generally uses higher sucrose concentrations which are administered for long periods of time (daily for weeks to months) (e.g., see Fritz et al, 2014;Gritz et al, 2016;Patkar et al, 2017).…”
mentioning
confidence: 99%
“…Nonetheless, taking in mind that the evaluation of the effectiveness of conventional AD treatment should be done considering the delay in its therapeutic effects, studies should go beyond short-term evaluations, assessing long-term consequences of treatment in animal models that better mimic AUD patient conditions [109]. Thus, unlike studies using acute treatments, authors that evaluated chronic and subchronic escitalopram, sertraline, paroxetine, fluoxetine (SSRIs), and duloxetine, dual serotonin/norepinephrine reuptake inhibitor (SNRI) treatments found that, along the treatment period, animals showed lower alcohol intake levels, but cessation of treatment produced a restoration of basal alcohol consumption [110][111][112]. Ho et al [110] also found an augmentation in alcohol intake in depressed animals once treatment with escitalopram ceased.…”
Section: Preclinical Evidence Of Antidepressant Treatment Improves Almentioning
confidence: 99%
“…Thus, unlike studies using acute treatments, authors that evaluated chronic and subchronic escitalopram, sertraline, paroxetine, fluoxetine (SSRIs), and duloxetine, dual serotonin/norepinephrine reuptake inhibitor (SNRI) treatments found that, along the treatment period, animals showed lower alcohol intake levels, but cessation of treatment produced a restoration of basal alcohol consumption [110][111][112]. Ho et al [110] also found an augmentation in alcohol intake in depressed animals once treatment with escitalopram ceased. Interestingly, authors also found the same effect in animals under combination of AD (escitalopram) and anti-relapse (acamprosate) treatments.…”
Section: Preclinical Evidence Of Antidepressant Treatment Improves Almentioning
confidence: 99%